2021
DOI: 10.3389/fneur.2021.645925
|View full text |Cite
|
Sign up to set email alerts
|

Are HFOs in the Intra-operative ECoG Related to Hippocampal Sclerosis, Volume and IQ?

Abstract: Temporal lobe epilepsy (TLE) is the most common form of refractory focal epilepsy and is often associated with hippocampal sclerosis (HS) and cognitive disturbances. Over the last decade, high frequency oscillations (HFOs) in the intraoperative electrocorticography (ioECoG) have been proposed to be biomarkers for the delineation of epileptic tissue but hippocampal ripples have also been associated with memory consolidation. Healthy hippocampi can show prolonged ripple activity in stereo- EEG. We aimed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that epileptic ripples are biomarkers of epileptogenicity in patients with epilepsy (Agudelo Valencia et al, 2021; Akiyama et al, 2011; Jacobs et al, 2010; Jiruska et al, 2010; Zijlmans et al, 2012). A greater percentage of ripples was found in the seizure onset zone than in normal tissue (González Otárula et al, 2019); thus, the EP hippocampus can be inferred based on the ripple rate in unilateral mesial temporal lobe epilepsy (Řehulka et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that epileptic ripples are biomarkers of epileptogenicity in patients with epilepsy (Agudelo Valencia et al, 2021; Akiyama et al, 2011; Jacobs et al, 2010; Jiruska et al, 2010; Zijlmans et al, 2012). A greater percentage of ripples was found in the seizure onset zone than in normal tissue (González Otárula et al, 2019); thus, the EP hippocampus can be inferred based on the ripple rate in unilateral mesial temporal lobe epilepsy (Řehulka et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In medial temporal lobe epilepsy, HFOs are linked to hippocampal sclerosis (Agudelo Valencia et al, 2021; Řehulka et al, 2019). More HFOs are detected via intraoperative EEG from the hippocampus in patients with hippocampal sclerosis than in patients with other epileptic conditions (Agudelo Valencia et al, 2021). Additionally, the non-epileptic hippocampi can be differentiated by a lower ripple rate than the epileptic hippocampi (Řehulka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation